Why are nit-2 transformants of Aspergillus nidulans partially derepressed? - M. A. Davis; M. J. Hynes (Fungal Genetics Reports, 1997)
The major nitrogen metabolite repression control genes of Aspergillus nidulans and Neurospora crassa are the areA and nit-2 genes respectively. Both genes encode transcriptional activators with highly conserved C2-X17-C2 zinc finger DNA binding domains which recognize similar WGATAR DNA sequences (Kudla et al., 1990 EMBO J. 9: 1355-1364; Fu and Marzluf, 1990 Proc. Natl. Acad. Sci USA 87: 5331-5335). We have shown previously that the N. crassa nit-2 gene can fully complement an areA loss-of-function mutation in A. nidulans, restoring growth on a wide variety of nitrogen sources. However, the nit-2 transformants are partially derepressed (Davis and Hynes, 1987 Proc. Natl. Acad. Sci. USA 84: 3753-3757).